Preparation of Ionic Silsesquioxanes with Regular Structures and Their Hybridization. (4th December 2012) - Kaneko, Yoshiro; Toyodome, Hisaya; Shoiriki, Miki; Iyi, Nobuo
Abstract : This paper deals with our recent studies on the preparation of ionic silsesquioxanes (SQs) with regular structures. Cationic ladder-like polySQs (PSQs) with hexagonally stacked structures were successfully prepared by the sol-gel reactions of amino group-containing organotrialkoxysilanes in strong acid aqueous solutions. Self-organization of an ion pair (a salt) prepared from the amino group in the organotrialkoxysilane and an acid is the key factor for the formation of such regular structures of the PSQs. It is also reported that the control of the conformational structure of the PSQs was performed by the introduction of the chiral moieties. In addition, we investigated the correlation between thep K a s of acid-catalysts and the structures of SQs prepared by the hydrolytic condensation of amino group-containing organotrialkoxysilane, that is, the use of the superacid aqueous solution resulted in the formation of cage-like octaSQ, while the ladder-like PSQs with hexagonally stacked structures were formed from the strong acid aqueous solutions under the same reaction conditions. Furthermore, anion-exchange behaviors of the cationic ladder-like PSQ were investigated with various organic and inorganic compounds, such as anionic surfactants, a polymer, and layered clay minerals, to obtain the functional hybrid materials.